PROSPEK PENGEMBANGAN UNIT USAHA BIBIT WANI TANPA BIJI HASIL METODE GRAFTING SEBAGAI UNIT USAHA INOVASI KAMPUS - Pradnyawathi, N.L.M.; Sardiana, I.K.; Darmiati, N.N.; Darmawati, I.A.P. (Buletin Udayana Mengabdi; Vol 21 No 3 (2022): Buletin Udayana Mengabdi, 2022)
The difficulty in obtaining seeds and the high price of seedlings prompted the implementation of the Campus Intellectual Product Business Development Program (PPUPIK) for superior local fruit seedlings of seedless BalineseWani at the Faculty of Agriculture, Udayana University. In order to support the successful development of the Seedless Wani Seed Business Unit, it is necessary to have a more in-depth study using a SWOT analysis. The research was conducted in Banjar Duren Taluh, Belimbing Village, Pupuan District, Tabanan Regency in April - August 2020. The study was conducted with a SWOT analysis to see the performance of business units by determining a combination of internal factors (strength and weakness) with external factors (opportunity and threats).  Furthermore, the EFI and EFE matrices are made. The results of the two matrices are then entered into a qualitative model, namely the SWOT matrix to formulate the company's competitive strategy. Based on the results of the EFE and EFE value analysis, the Seedless Wani Seed Business Unit is in cell one where in this position the business unit can implement a growth strategy with vertical integration by taking over the supplier function or by taking over the function of the distributor. This is the main strategy for companies that have a strong and highly competitive market position.   Keywords:  Bali local fruit, Seedless wani seedling, SWOT analysis